An Evaluation of System End-User Support during Implementation of an Electronic Health Record Using the Model for Improvement Framework - Kiepek, Wendy; Sengstack, Patricia P. (Applied Clinical Informatics, 2019)
Background Electronic health record (EHR) system implementation is complex. Strong support for clinicians and other end-users during the initial phase of implementation requires dedicated resources and commitment to ensure a smooth transition, reduce frustration, and assist in adoption.Objectives Evaluate end-user support processes and personnel employed during the initial phase of EHR implementation at an academic medical center and identify facilitators of success, challenges, and lessons learned.Methods Using the model for improvement framework, this case report describes the activities that follow the concepts of planning, doing, studying, and acting (PDSA) when providing on-site support to system end users during an EHR implementation in a complex health care system.Results Strengths included engaged and supportive leadership, use of internal support personnel, use of zone leaders, daily huddles for effective dissemination of information, and an evaluation survey tool to provide data supporting rapid changes in support personnel allocation. Challenges primarily surrounded the management of over 1,000 external support personnel which included limited EHR system knowledge, scheduling, and transportation logistics.Conclusion Implementation of EHR systems continues. Supporting end users is one aspect of these complex projects that require dedicated resources to manage effectively. Organizations taking a more proactive approach, based on learning from experiences, as well as from other health care organizations, can improve their ability to take on this challenge armed with best practices and lessons learned.
Keywords: implementation and deployment; clinical information systems; electronic health records and systems; leadership (enterprise level); facilitators and barriers; adoption; evaluation; process improvement; satisfaction